2020
DOI: 10.1002/adma.202003915
|View full text |Cite
|
Sign up to set email alerts
|

Human‐Recombinant‐Elastin‐Based Bioinks for 3D Bioprinting of Vascularized Soft Tissues

Abstract: Bioprinting has emerged as an advanced method for fabricating complex 3D tissues. Despite the tremendous potential of 3D bioprinting, there are several drawbacks of current bioinks and printing methodologies that limit  the ability to print elastic and highly vascularized tissues. In particular, fabrication of complex biomimetic structure that are entirely based on 3D bioprinting is still challenging primarily due to the lack of suitable bioinks with high printability, biocompatibility, biomimicry, and proper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 43 publications
3
109
0
Order By: Relevance
“…High mechanical force or pressure needs to be applied to push the high viscosity hydrogel out from the nozzle. A previous study on the shear-thinning properties of gelatin-elastin bioinks by using extrusion-based bioprinting indicated that the level of shear stress increases when the pressure in the extrusion piston increases [ 72 ]. Figure 5 a shows the shear stress region in the syringe during the printing procedure.…”
Section: Strategies To Achieve Optimal Printability Quality For 3dmentioning
confidence: 99%
See 2 more Smart Citations
“…High mechanical force or pressure needs to be applied to push the high viscosity hydrogel out from the nozzle. A previous study on the shear-thinning properties of gelatin-elastin bioinks by using extrusion-based bioprinting indicated that the level of shear stress increases when the pressure in the extrusion piston increases [ 72 ]. Figure 5 a shows the shear stress region in the syringe during the printing procedure.…”
Section: Strategies To Achieve Optimal Printability Quality For 3dmentioning
confidence: 99%
“…However, the shape fidelity of the hydrogel can be improved by printing a complex structure of the hydrogels [ 72 ]. The main concept of 3D-bioprinting is to print the hydrogel layer-by-layer until it forms a composite scaffold.…”
Section: Strategies To Achieve Optimal Printability Quality For 3dmentioning
confidence: 99%
See 1 more Smart Citation
“…The blending of MeTro with other polymers has been explored to enhance their elasticity. For instance, it was blended with GelMA to obtain elastic bioinks that were used for 3D printing of vascularized cardiac constructs that showed endothelium barrier function and spontaneous beating of cardiac muscle cells [ 36 ].…”
Section: Hydrogels Inspired By the Extracellular Matrixmentioning
confidence: 99%
“…Chemically crosslinked, cell-compatible elastin-like hydrogels have been constructed carefully designing the crosslinking reactions. Weiss et al synthesized methacrylate derivative of tropoelastin, the monomeric form of elastin [ 8 , 9 ]. This derivative is photo-crosslinked to form hydrogels within a minute upon ultraviolet (UV) irradiation.…”
Section: Introductionmentioning
confidence: 99%